2006
DOI: 10.1021/jp0639546
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivity of Si(111)−H in Ambient

Abstract: Second harmonic generation rotational anisotropy (SHG-RA) provides a convenient means to monitor the chemical state of the Si surfaces and to follow the conversion of a H-terminated surface to SiO 2 by oxidation as a function of time in ambient. SHG at 800 nm is sensitive to changes in the surface electronic properties induced by oxidation, and it probes both the initial stage of oxidation and the logarithmic oxide growth. We found that intense, ultrashort (4 ps) 800 nm laser pulses accelerate the initial stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Table summarizes the water contact angle values (θ water ) of Si(111) substrates with various surface functionalization (Scheme ). Beginning with the NH 4 F etched Si(111), the atomically flat Si(111)–H results in a hydrophobic surface shown by a large water contact angle (99 ± 6°). , Subsequently, the silicon is slowly oxidized to yield a hydrophilic Si–O x layer on the surface, resulting in the decrease of the contact angle (θ water ≈ 56.2 ± 1.7°). As shown in Table , the methylated surface [Si(111)–CH 3 ] exhibits a high water contact angle (θ water ) of 110.8 ± 0.8°, indicating a very hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table summarizes the water contact angle values (θ water ) of Si(111) substrates with various surface functionalization (Scheme ). Beginning with the NH 4 F etched Si(111), the atomically flat Si(111)–H results in a hydrophobic surface shown by a large water contact angle (99 ± 6°). , Subsequently, the silicon is slowly oxidized to yield a hydrophilic Si–O x layer on the surface, resulting in the decrease of the contact angle (θ water ≈ 56.2 ± 1.7°). As shown in Table , the methylated surface [Si(111)–CH 3 ] exhibits a high water contact angle (θ water ) of 110.8 ± 0.8°, indicating a very hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
“… a Average ± standard deviation from three separate samples, two different spots for each sample. b Value from ref . …”
Section: Resultsmentioning
confidence: 99%
“…Previously, similar nonlinear-optical experiments were modeled by tensorial calculations (11)(12)(13), which are based on the symmetry of the underlying Si lattice. However, our data emphasize that chemistry takes place in real time at the atomic scale and that symmetry is an end result of chemical processes; i.e., it is not constant but evolves in time.…”
Section: Resultsmentioning
confidence: 99%
“…[4,21] We have demonstrated that the interfacial electronic structure of well prepared Si(111)-H, as determined by SHG, can be stable for >10 4 minutes! [4] (Fig. 2) However, intense laser illumination can lead to accelerated, photon-driven reactivity (Fig.…”
Section: Second Harmonic Spectroscopy Of Chemically Modified Semicondmentioning
confidence: 92%